Can a print‐based intervention increase screening for first degree relatives of people with colorectal cancer? A randomised controlled trial - Mariko Carey; Robert Sanson‐Fisher; Finlay Macrae; Emilie Cameron; David Hill; Catherine D'Este; Jody Simmons; Christopher Doran (Elsevier, 2016)
Abstract Objective: To test the effectiveness of a targeted print‐based intervention to improve screening adherence in first degree relatives of people with colorectal cancer (CRC). Methods: People with CRC and their adult first degree relatives were identified through a population‐based cancer registry and randomly allocated as a family unit to the intervention or control condition. The control group received general information about CRC screening. The intervention group received printed advice regarding screening that was targeted to their risk level. Screening adherence was assessed at baseline and at 12 months via self report. Results: 752 (25%) index cases and 574 (34%) eligible first degree relatives consented to take part in the trial and completed baseline interviews. At 12 months, 58% of first degree relatives in the control group and 61% in the intervention group were adherent to screening guidelines (mixed effects logistic regression group by time interaction effect =2.7; 95%CI=1.2-5.9; P=0.013). Subgroup analysis indicated that the intervention was only effective for those with the lowest risk. Conclusions: Provision of personalised risk information may have a modest effect on adherence to CRC screening recommendations among first degree relatives of people diagnosed with CRC. Implications: Improved strategies for identifying and engaging first degree relatives are needed to maximise the population impact of the intervention.